The Use of Problem Based Learning Model to Improve Student’s Learning Outcomes on Fifth Grade - Dyah Kartika Sari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to improve learning outcomes of Fifth Grade students of Elementary School in the learning Fourth Theme through the application of the Problem-Based Learning (PBL) model. This was a classroom action research. The study involves Fifth Grade students of the elementary school as the research subject. The data were collected through observation with test and nontest. This research is using two cycles. The results of the study show that: (a) the application of the PBL model is capable of improving the student’s outcome (b) In the first cycle, there was five students who passed the grade, that the average value is 62,5 %. (c) In the second cycle, there was an improvement for the learning outcomes, that the average value is 75%, which six students passed the grade. (d) the students’ learning outcomes after the application of the PBL model namely the number of students who reach the KKM as much as 6 students (75%) from totally 8 students.